Autologous bone marrow mononuclear cell transplantation for osteonecrosis of the femoral head in post-covid-19 syndrome: A case series - Franco, Bruno Adelmo [UNESP]; Garrido, Saulo [UNESP]; Faleiro, Thiago; Veiga, Davi; Daltro, Paula; Pereira, Beatriz; Daltro, Gildásio (Elsevier, 2025)
Introduction: The emergence of femoral head osteonecrosis in post-COVID-19 patients, possibly related to corticosteroid use, prompted the search for pathophysiological understanding and minimally invasive treatments, such as autologous mesenchymal cell transplantation. Methodology: Fifteen patients with post-COVID-19 femoral head osteonecrosis between 2021 and 2023 participated. A total of 100 mL of bone marrow was aspirated and processed using the SEPAX® system. The cells were tested for viability using an anti-CD34 antibody and characterized by flow cytometry and clonogenic assays. Postoperative care involved weight-bearing restrictions and clinical monitoring. This is a case series, level of evidence IV. Results: Thirteen hips of patients affected by mild to moderate COVID-19 were operated on; 40 % of hospitalized patients did not require mechanical ventilation. 66.7 % received corticosteroids. Necrosis mainly occurred in the right hip, with an average necrotic area of 40 %. Conclusions: COVID-19 infection and corticosteroid use and duration are related to an increased incidence of osteonecrosis. Patients who did not use corticosteroids also developed osteonecrosis. Treatment with autologous bone marrow progenitor cells reduced pain and improved Harris Hip Score.